Impact of COVID-19 on Pediatric Asthma: Practice Adjustments and Disease Burden - Papadopoulos, NG (2020)
It is unclear whether asthma may affect susceptibility or severity of coronavirus disease 2019 (COVID-19) in children and how pediatric asthma services worldwide have responded to the pandemic.